IEEE 802.11n: Joint modulation‐coding and guard interval adaptation scheme for throughput enhancement. (5th February 2020) - Patil, Pravinkumar; Patil, Meenakshi; Itraj, Santosh; Bombale, Uttam
Summary: IEEE 802.11n is a high‐speed wireless broadband local area networking standard. IEEE 802.11n‐based devices are using some kind of adaptive modulation‐coding (AMC) scheme to adjust its transmission rate according to the radio channel condition. In these devices, however, the concept of guard interval adaptation is not been considered. Normally, orthogonal frequency division multiplexing (OFDM) technology‐based systems are using the guard interval much greater than the length of the channel impulse response. However, many previous works have shown that the choice of the larger guard interval is inefficient in terms of achievable throughput. IEEE802.11n supports using two guard intervals (short = 400 ns or long = 800 ns). Indeed, the shorter guard interval evidently results in intersymbol interference (ISI) and intercarrier interference (ICI), but the gain offered by shortened guard interval may exceed the loss caused by interference. In this paper, we propose a novel but simple solution for the guard interval adaptation joint with an adaptive modulation‐coding scheme to optimize the throughput performance of a wireless local area network (WLAN) system. This paper aims to analyze the effect of joint adaptive modulation‐coding and the guard interval (JAMCGI) algorithm on the WLAN system under bit‐error‐rate (BER) constraints. Simulation results and their analysis show a significant increase in the throughput performance of the WLAN system with our proposed algorithm. Abstract : In this paper, we propose a novel but simple solution for the guard interval adaptation joint with an adaptive modulation‐coding scheme to optimize the throughput performance of a wireless local area network (WLAN) system. This paper aims to analyze the effect of joint adaptive modulation, coding, and the guard interval (JAMCGI) algorithm on the WLAN system, under bit‐error‐rate (BER) constraints. Simulation results and their analysis show a significant increase in the throughput performance of the WLAN system with our proposed algorithm.